2007
DOI: 10.1007/s11250-007-9107-0
|View full text |Cite
|
Sign up to set email alerts
|

Endemic status of Trypanosoma evansi infection in a horse stable of eastern region of India – a field investigation

Abstract: Diagnosis of Trypanosoma evansi infection in a horse stable of Eastern Region of India on the basis of examination of Giemsa stained blood smears have been done. A high percentage (12.74%) of horses of this stable was found suffering from T evansi infection. This high prevalence of T evansi in horses, in this area could be considered as an alarming situation which has never been explored previously in horses of Eastern Region of India. After a period of 2 months and 18 days of treatment with quinapyramine sulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It has the largest geographical distribution and widest range of hosts amongst the pathogenic trypanosomes (Nurulaini et al 2007;Laha and Sasmal 2008;Dargantes et al 2009). Recently, a report indicated that humans may be infected with T. evansi (Truc et al 2007).…”
mentioning
confidence: 99%
“…It has the largest geographical distribution and widest range of hosts amongst the pathogenic trypanosomes (Nurulaini et al 2007;Laha and Sasmal 2008;Dargantes et al 2009). Recently, a report indicated that humans may be infected with T. evansi (Truc et al 2007).…”
mentioning
confidence: 99%
“…Other publications reported higher seroprevalence rates, 73% were found in Brazil using IFAT (Herrera et al, 2004) and 92% were demonstrated in Philippine (Dargantes et al, 2009). Some studies report lower seroprevalence, as is the case in Malaysia (13%) (ELshafie et al, 2013) and India (27%) (Laha and Sasmal, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Overall species wise sero-prevalence survey in Karnataka showed the dominant statistics with buffalo of 25 % S.P, followed by cattle with 18.03 % S.P, Donkey with 5.5% S.P and Horse with 6.25% S.P (Table I). 24 . In Karnataka, no significant variations were observed between sero-positivity and negativity among two tests (χ²=0.079, df=1, p>0.05).…”
Section: Resultsmentioning
confidence: 99%